COEXISTENCE OF GAP AND SEPTATE JUNCTIONS IN AN INVERTEBRATE EPITHELIUM - Hudspeth, A. J. (The Rockefeller University Press, 1971)
The intercellular junctions of the epithelium lining the hepatic caecum of Daphnia were examined. Electron microscope investigations involved both conventionally fixed material and tissue exposed to a lanthanum tracer of the extracellular space. Both septate junctions and gap junctions occur between the cells studied. The septate junctions lie apically and resemble those commonly discerned between cells of other invertebrates. They are atypical in that the high electron opacity of the extracellular space obscures septa in routine preparations. The gap junctions are characterized by a uniform 30 A space between apposed cell membranes. Lanthanum treatment of gap junctions reveals an array of particles of 95 A diameter and 120 A separation lying in the plane of the junction. As this pattern closely resembles that described previously in vertebrates, it appears that the gap junction is phylogenetically widespread. In view of evidence that the gap junction mediates intercellular electrotonic coupling, the assignment of a coupling role to other junctions, notably the septate junction, must be questioned wherever these junctions coexist.